Chromosome-scale assemblies of plant genomes using nanopore long reads and optical maps. (November 2018) - Belser, Caroline; Istace, Benjamin; Denis, Erwan; Dubarry, Marion; Baurens, Franc-Christophe; Falentin, Cyril; Genete, Mathieu; Berrabah, Wahiba; Chèvre, Anne-Marie; Delourme, Régine; Deniot, Gwenaëlle; Denoeud, France; et al.
Abstract Plant genomes are often characterized by a high level of repetitiveness and polyploid nature. Consequently, creating genome assemblies for plant genomes is challenging. The introduction of short-read technologies 10 years ago substantially increased the number of available plant genomes. Generally, these assemblies are incomplete and fragmented, and only a few are at the chromosome scale. Recently, Pacific Biosciences and Oxford Nanopore sequencing technologies were commercialized that can sequence long DNA fragments (kilobases to megabase) and, using efficient algorithms, provide high-quality assemblies in terms of contiguity and completeness of repetitive regions1–4 . However, even though genome assemblies based on long reads exhibit high contig N50s (>1 Mb), these methods are still insufficient to decipher genome organization at the chromosome level. Here, we describe a strategy based on long reads (MinION or PromethION sequencers) and optical maps (Saphyr system) that can produce chromosome-level assemblies and demonstrate applicability by generating high-quality genome sequences for two new dicotyledon morphotypes, Brassica rapa Z1 (yellow sarson) andBrassica oleracea HDEM (broccoli), and one new monocotyledon, Musa schizocarpa (banana). All three assemblies show contig N50s of >5 Mb and contain scaffolds that represent entire chromosomes or chromosome arms. Assembling genomes to chromosome scale remains a challenge. Now, a study reports a strategy based on nanopore long reads and optical maps and uses it to produce high-quality chromosome-scale assemblies for the genomes of yellow sarson, broccoli and banana.